The Relationship between Spirituality and Depression Among the Elderly in Indonesia - Mahwati, Yeni (Makara Journal of Health Research, 2017)
Background: Studies have shown that there is an association between spirituality and better physical and mental health. Depression has one of the highest prevalence amongst the mental health illnesses in the elderly, and it can lead to poor physical health. This study aims to determine the relationship between spirituality and depression. Methods: Data was obtained from the 4th Indonesian Family Life Survey, that was conducted in 2007; the total study sample included 3,103 elderly Indonesians. Logistic regression was performed to determine the relationship between spirituality and depression.  Results: This study found that the prevalence of depression was 7.2%, with the largest proportion of those being ≥ 70 years, female, less educated, unemployed, elderly with multimorbidities, unmarried, and less spiritual. Logistic regression analysis showed a strong relationship between spirituality and depression (odds ratio= 1.869; 95% confidence interval; 1.422 to 2.458) after it was controlled for all variables. Conclusions: This study found that spirituality has a significant relationship with rates of depression. The government needs to develop a program that strengthens spirituality to improve mental health in the elderly.